Where Do Early Career Researchers Stand on Open Science Practices? A Survey Within the Max Planck Society - Toribio-Flórez, Daniel; Anneser, Lukas; deOliveira-Lopes, Felipe Nathan; Pallandt, Martijn; Tunn, Isabell; Windel, Hendrik; , on behalf of Max Planck PhDnet Open Science Group (Frontiers in Research Metrics and Analytics, 2021)
Open Science (OS) is of paramount importance for the improvement of science worldwide and across research fields. Recent years have witnessed a transition towards open and transparent scientific practices, but there is still a long way to go. Early-career researchers (ECRs) are of crucial relevance in the process of steering towards the standardization of OS practices, as they will become the future decision-makers of the institutional change that necessarily accompanies this transition. Thus, it is imperative to gain insight into the ECRs' on OS practices. Under this premise, the Open Science group of the Max Planck PhDnet designed and conducted an online survey to assess the stance towards OS practices of early-career researchers from the Max Planck Society. As one of the leading scientific institutions for basic research worldwide, the Max Planck Society provides a representative population of researchers from multiple scientific fields, englobed into three sections: Biomedical sciences, Chemistry, Physics and Technology, and Human and Social sciences. From an approximate total population of 5100 doctoral candidates affiliated with the Max Planck Society, the survey collected responses from 568 doctoral candidates. The survey assessed self-reported knowledge, attitudes, and implementation of different OS practices, namely Open Access Publications, Open Data, Pre-Registrations, Registered Reports, and Replication Studies. ECRs seemed to hold a generally positive view towards these different practices and to be interested in learning more about them. Furthermore, we found that ECRs’ knowledge and positive attitudes predicted the extent to which they implemented these OS practices, although levels of implementation were rather low in the past. We observed differences and similarities between scientific sections, which we discuss in terms of need and feasibility to apply these OS practices in specific scientific fields, but additionally in relation to the incentive systems that shape scientific communities. Lastly, we discuss the implications that these results can have for the training and career advancement of ECRs, and ultimately, for the consolidation of OS practices.